Pengaruh religiositi, penaakulan moral dan penghayatan nilai murni terhadap tingkah laku prososial dalam kalangan pelajar di Banda Aceh, Indonesia - , Safrilsyah (2018)
The phenomenon of decline in prosocial behaviors among students is alarming in Indonesia. This is seen as the decline of values and morals and the violation of society norms amongst students. Therefore, this study focuses on the relationship between religiosity and prosocial behavior whereby moral reasoning and appreciation of pure values are used as mediator variables. The methodology of this study used cross sectional survey. The data were collected using questionnaire, religiosity was measured using the Secondary Student Islamic Education Scale (SPPIP-M) from Azma (2006), Moral Reasoning was measured using the Honorable Scheme of Identity Scheme (UPSTA) from Aswati Hamzah (2007), appreciation of pure values was measured using pure values internalization from Mohamad Khairi Othman (2011) and prosocial behavior was measured using the Prosocial Tendencies Measure (PTM) built by Carlo (2010). The sampling method used multiple tier sampling techniques. Students were randomly selected among 649 students at eight high schools in Banda Aceh, Indonesia. Data were analyzed based on Pearson correlation and multiple regression. The findings show that there is a significant positive relationship between religiosity (r=.606;p<.00), moral reasoning (r=.294;p<.00) and appreciation of pure values (r=.668;p<.00) with student's prosocial behavior. The findings also showed significant influence between the main variables dimensions and student demographics on prosocial behavior (R2=.622;p<.00). In addition, the findings also prove that the pursuit of pure values is only partial mediator between the religiosity and prosocial behavior of the students. The conclusion of the study shows that the level of religiosity, moral reasoning and appreciation of pure values affects prosocial behavior. Furthermore, only the pursuit of pure values serves as a partial mediator to improve religiosity practice as the basis of the formation of student's prosocial behavior.